Quality of websites of Palestinian schools in Gaza - Abuhassna, Hassan M. M.; Mohd Daud, Shaffe (IRPN Press, 2014)
A website serves as a gateway that provides useful content and links to various sites and their features through the Internet. Accordingly, a school website serves as an effective platform on which to publicize activities implemented for students, teachers, and other interested parties within the academe. An excellent school website can be built through cooperation between the school administrator and the webmaster; such cooperation facilitates the effective communication of information to students and other visitors of the website. This study aims to describe the quality of websites maintained by 40 secondary schools in the Gaza (Palestine) region. This study employs a descriptive survey that uses questionnaires that cover aspects of quality in the construction of a school website. The questionnaires are distributed to webmasters in secondary schools in Gaza through e-mail or post (for school websites that do not disclose their e-mail addresses). The websites used in this study are only those accessible to the public. All findings are collected and summarized to clearly describe the quality of the websites of Gaza schools.